On the solvability of the dirichlet problem for elliptic nondivergent equations of the second order in a domain with conical point - Borsuk, M. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of solvability of the Dirichlet problem for second-order linear and quasilinear uniformly elliptic equations in a bounded domain whose boundary contains a conical point. We prove new theorems on the unique solvability of a linear problem under minimal smoothness conditions for the coefficients, right-hand sides, and the boundary of the domain. We find classes of solvability of the problem for quasilinear equations under natural conditions.